miR-451 Loaded Exosomes Are Released by the Renal Cells in Response to Injury and Associated With Reduced Kidney Function in Human - Kumari, Manju; Mohan, Aradhana; Ecelbarger, Carolyn M.; Saxena, Anita; Gupta, Amit; Prasad, Narayan; Tiwari, Swasti (Frontiers in Physiology, 2020)
Micro-RNAs (miRs) encapsulated inside urinary exosomes (uEs) have the potential as early biomarkers. Previously, we reported that a rise in uE miR-451 predicted albuminuria in diabetic rats; however, whether the rise was protective or detrimental, and occurred in response to injury or general hyperglycemia, was unknown. To address this, we studied both human and rat models of renal disease. In humans, uE miR-451 was approximately twofold higher in subjects with early-stage chronic kidney disease (CKD; serum creatinine < 2.0 mg/dl; n = 28), as compared to age-matched healthy controls (n = 23), and had a significant negative correlation with estimated glomerular filtration rate (eGFR) (r2 = −0.10, p = 0.01). Subgroup analysis of CKD subjects showed that those without diabetes had slightly (∼30%) but significantly higher uE miR-451 as compared to those with diabetes, with no differences in albumin excretion, eGFR, serum sodium, and potassium. Using human proximal tubule (hPT) cells, we found that locked nucleic acid (LNA) inhibition of miR-451 resulted in a significant increase in the messenger RNA (mRNA) expression of kidney-injury-associated miR-451 targets, e.g., CAB39, TBX1, and YWHAZ, as compared to treatment with a control LNA. Moreover, hPT cells and their secreted exosomes showed an increase in miR-451 in response to mechanical injury but not high glucose (20 versus 5 mM). For further proof of concept, in diabetic rats, we showed that atorvastatin (AT), a treatment proven to attenuate renal injury without affecting systemic glucose levels, reduced uE miR-451 with the concomitant restoration of renal miR-451. These data elucidate the stimuli for renal miR-451 expression and exosomal release and support its role as a therapeutic target and early biomarker for renal injury in humans.